Catalytic attenuating agent based on MXene nanosheet material, modified rigid polyurethane foam composite material and preparation method of catalytic attenuating agent and modified rigid polyurethane foam composite material

By using catalytic attenuators based on MXene nanosheet materials in rigid polyurethane foam, the problems of material flammability and environmental hazards of traditional flame retardants are solved, and the efficient flame retardant and catalytic attenuation of the material are achieved.

CN119746845APending Publication Date: 2025-04-04XIAMEN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411919505.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Rigid polyurethane foam materials have fire safety hazards during use, and fire accidents caused by flammability occur frequently. Traditional flame retardants have problems such as volatile, toxic gases, and potential environmental hazards.

Method used

Using a catalytic attenuator based on MXene nanosheet materials, MXene is combined with biomass materials (such as chitosan) and MnO2 catalysts to form a sandwich structure through electrostatic adsorption method, and introduced into rigid polyurethane foam to exert the sheet barrier and catalytic activity of MXene and MnO2, and reduce the release of toxic flue gas.

Benefits of technology

It effectively reduces the release of toxic flue gas during pyrolysis and combustion of rigid polyurethane foam, improves the flame retardant performance and catalytic attenuation effect of the material, while maintaining good mechanical properties and environmental friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746845A_ABST
    Figure CN119746845A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of materials. The invention provides a catalytic attenuating agent based on an MXene nanosheet material, which is characterized in that the catalytic attenuating agent comprises a carrier layer, an attenuating functional layer and a catalytic blocking layer, the carrier layer is an MXene nanosheet, the attenuating functional layer is formed by depositing a biomass material on the surface of the MXene nanosheet through electrostatic adsorption, and the catalytic blocking layer is formed by depositing the biomass material on the surface of the MXene nanosheet through electrostatic adsorption. The catalytic barrier layer is formed by adsorbing MnO2 on the surface of the attenuated functional layer through static electricity, so that a core-shell layer-outer layer sandwich structure is formed. The catalytic attenuating agent combines multiple functions of catalytic attenuation, catalytic char formation, lamellar barrier and the like, can improve the decomposition efficiency of the rigid polyurethane foam material on toxic gases (such as CO, HCN and the like) in the combustion process, and reduces the release of harmful smoke particles and toxic gases. The organic-inorganic modified catalytic attenuating agent has wide application potential, and can show good flame retardant property, catalytic attenuating effect and environmental friendliness especially in a rigid polyurethane foam flame retardant material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material technology, and in particular to a catalyst detoxifier based on MXene nanosheet materials and a modified rigid polyurethane foam composite material and a preparation method thereof. Background Art

[0002] With the development of modern industry, rigid polyurethane foam (RPUF) materials have been widely used in many fields such as construction, automobiles, and aviation due to their excellent thermal insulation performance, light weight, and high strength. However, rigid polyurethane foam materials have certain fire safety hazards during use. Frequent fire accidents caused by their flammability pose a major threat to personal safety and property. Therefore, improving the flame retardant properties of rigid polyurethane foam materials and reducing the emission of toxic gases produced by combustion have become technical problems that need to be solved urgently.

[0003] At present, there are many flame retardants on the market that have been used in polyurethane foam materials, such as halogen flame retardants, phosphorus flame retardants and inorganic flame retardants. However, traditional flame retardants have some defects, including easy volatility at high temperatures, generation of toxic gases, and potential harm to the environment. In addition, the use of some flame retardants will have a negative impact on the mechanical properties of the material, resulting in a decrease in the overall performance of rigid polyurethane foam materials.

[0004] In recent years, the catalytic detoxification properties of polymer materials have received increasing attention. This technology promotes the decomposition of toxic gases through catalytic reactions and effectively reduces the harmful substances released during combustion. In particular, the application of catalytic detoxifiers is particularly important in fires and the environmental pollution they cause. MXene, as a new type of two-dimensional nanomaterial, has attracted much attention due to its excellent conductivity, high specific surface area and excellent catalytic performance. The structural characteristics of MXene give it rich surface functional groups, providing sufficient active centers for catalytic reactions. In addition, the layered structure of MXene helps to improve the thermal stability and mechanical properties of the material, so that it can still maintain excellent catalytic activity under high temperature conditions. Manganese dioxide (MnO2) is a commonly used catalyst widely used in gas purification and pollutant degradation. Due to its good redox properties and high catalytic activity, it can effectively promote the decomposition of toxic gases (such as carbon monoxide and hydrocyanic acid) and reduce their harm to the environment. Therefore, it is of great significance to combine modified MXene with MnO2 and expand its application to other fields. However, there has been no research on the preparation of a sandwich structure formed by combining MXene with biomass materials (such as chitosan CHS) and MnO2 catalyst by electrostatic adsorption method and its related research on smoke suppression and toxicity reduction performance.

[0005] In view of this, the applicant filed this application after studying the existing technology. Summary of the invention

[0006] In order to solve the above technical problems, the first purpose of the present invention is to provide a catalytic detoxifier based on MXene nanosheet materials, which has good dispersibility in isocyanate, so that when introduced into rigid polyurethane foam, it can give full play to the sheet barrier and catalytic activity of MXene and MnO2 nanosheets, and give full play to the good catalytic carbonization performance of biomass materials, thereby effectively reducing the release of toxic flue gas during pyrolysis and combustion of rigid polyurethane foam materials.

[0007] The second object of the present invention is to provide a method for preparing a catalyst detoxifier based on MXene nanosheet materials. The method is simple and easy to implement, and can effectively prepare a catalyst detoxifier with a stable structure and good dispersibility in isocyanate.

[0008] The third object of the present invention is to provide a modified rigid polyurethane foam composite material, which has good flame retardant properties, catalytic detoxification effect and environmental friendliness.

[0009] The fourth object of the present invention is to provide a method for preparing a modified rigid polyurethane foam composite material, which is simple and easy to implement and can effectively prepare a modified rigid polyurethane foam composite material with excellent properties.

[0010] The present invention adopts the following technical solutions: The present invention provides a catalytic detoxifier based on MXene nanosheet material, comprising a carrier layer, a detoxification functional layer and a catalytic barrier layer, wherein the carrier layer is a MXene nanosheet, the detoxification functional layer is composed of biomass material deposited on the surface of the MXene nanosheet by electrostatic adsorption, and the catalytic barrier layer is composed of MnO2 electrostatically adsorbed on the surface of the detoxification functional layer, thereby forming a core-shell-outer layer sandwich structure.

[0011] In this scheme, the core material is the MXene nanosheet carrier layer, which has a large specific surface area and abundant active centers, as a supporting material; the shell layer is a natural and environmentally friendly biomass material, which has the function of promoting carbonization, as a detoxification functional layer; the outer layer is a MnO2 catalytic barrier layer, which can show excellent barrier and catalytic effects. The electrostatic adsorption method can achieve selective adsorption of molecules or nanoparticles with specific charges, thereby improving the catalytic detoxification performance of the material.

[0012] Furthermore, the thickness of the MXene nanosheet is 1-10 nanometers to ensure its good layered structure and catalytic performance.

[0013] Furthermore, the biomass material includes chitosan, cationic starch or plant protein.

[0014] Furthermore, the crystal structure of the MnO2 is δ-MnO2. δ-MnO2 has a layered structure and a negatively charged surface, which can enhance its catalytic activity and interaction with other components.

[0015] A method for preparing a catalyst detoxifier based on MXene nanosheet materials as described above, comprising the following steps: S1. Preparation of MXene nanosheets: Pour hydrochloric acid solution into a polytetrafluoroethylene reactor, add lithium fluoride, add carbon, aluminum and titanium after it is dissolved, react at a set temperature, ultrasonically peel, centrifuge and dry; S2. Preparation of δ-MnO2 nanosheets: potassium permanganate is completely dissolved in deionized water, and ethyl acetate is added after it is completely dissolved, and stirred and reacted at a temperature not exceeding 90°C until the red color completely disappears, and then centrifuged, washed, and dried; S3, preparing a detoxification functional layer: dispersing the MXene nanosheets obtained in step S1 in deionized water, then dropping a chitosan aqueous solution, centrifuging the suspension after mechanical stirring, and washing to obtain an intermediate product; S4. Preparation of a catalytic barrier layer: Under stirring and ultrasonic action, the intermediate product obtained in step S3 is dispersed in deionized water, and then dripped into the suspension of MnO2 obtained in step S2. After stirring, the suspension is centrifuged, washed, and dried.

[0016] Furthermore, in step S1, the concentration of the hydrochloric acid solution is 8-10 mol / L, the set temperature is 35-45°C, the reaction time is 40-50h, and the ultrasonic stripping and centrifugal separation treatments are performed for no less than 20 times.

[0017] Furthermore, in step S3, the pH value of the chitosan aqueous solution is 5-5.5, and the acid used to adjust the pH value of the chitosan aqueous solution is dilute hydrochloric acid or dilute sulfuric acid.

[0018] Further, in step S3, the concentration of MXene is 0.1wt%-0.5wt%, and the concentration of chitosan is 0.1wt%-1wt%.

[0019] The present invention further provides a modified rigid polyurethane foam composite material, comprising any of the above-mentioned catalyst detoxifiers based on MXene nanosheet materials.

[0020] In this embodiment, the added amount of the catalyst detoxifier is 0.5-5wt% of the total mass of the rigid polyurethane foam material.

[0021] A method for preparing the modified rigid polyurethane foam composite material as described above comprises the following steps: a: adding an organotin catalyst, an amine catalyst, silicone oil, deionized water and triethanolamine to the polyol, stirring evenly to obtain a white material; b: Add the catalyst detoxifier to the isocyanate, disperse it by mechanical stirring, and then pour the dispersion into the white material obtained in step a. After stirring, pour the mixture into a mold, allow it to foam freely, and mature it in an oven.

[0022] By adopting the above technical solution, the present invention can achieve the following technical effects: 1. The catalytic detoxification agent based on MXene nanosheet material provided by the present invention has a layered structure that is reasonably designed to ensure stability under high temperature and complex chemical environments. At the same time, the electrostatic adsorption method is used, and the charge is controlled by the pH value of the solution, which can selectively adsorb molecules or nanoparticles with specific charges, thereby improving the catalytic detoxification performance of the material. In addition, the preparation method is simple and easy, reducing the complex steps in the production process.

[0023] 2. The biomass materials such as chitosan used in the present invention have good biocompatibility and effective degradation ability, meet the requirements of green chemistry, and can give full play to its effect of promoting carbonization; in addition, the high specific surface area and rich surface functional groups of MXene provide sufficient active centers for catalytic reactions, and the good redox properties of MnO2 can effectively promote the decomposition of toxic gases (such as carbon monoxide, hydrocyanic acid, etc.), thereby giving full play to its sheet barrier and catalytic effects.

[0024] 3. The catalyst detoxifier prepared by the present invention has good dispersibility in isocyanate, ensuring uniform distribution in practical applications and avoiding reduced activity due to aggregation. This feature significantly improves the overall catalytic performance of the catalyst detoxifier in rigid polyurethane foam and effectively reduces the release of harmful gases during combustion. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 A schematic diagram of the layered structure of the catalyst detoxifier based on MXene nanosheet material of the present invention; Figure 2 This is a transmission electron microscope image of the ultrathin MXene prepared in Example 1 of the present invention; Figure 3This is the X-ray diffraction pattern of MXene@CHS@MnO2 prepared in Example 1 of the present invention; Figure 4 This is a transmission electron microscopy image of MXene@CHS@MnO2 prepared in Example 1 of the present invention; Figure 5 This is the EDX spectrum of MXene@CHS@MnO2 prepared in Example 1 of the present invention; Figure 6 This is the line scan curve of MXene@CHS@MnO2 prepared in Example 1 of the present invention; Figure 7 It is a photo of MXene and MXene@CHS@MnO2 powders prepared in Example 1 of the present invention; Figure 8 Pure rigid polyurethane foam and rigid polyurethane foam prepared in Example 2 of the present invention. Force-displacement curve of MXene@CHS@MnO2 nanocomposite material. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0028] Example 1 like Figure 1 As shown, the present invention provides a method for preparing a catalyst detoxifier based on MXene nanosheet materials, the steps are as follows: S1: Slowly drain 150ml of concentrated hydrochloric acid into 50ml of deionized water to prepare a hydrochloric acid solution, and then pour the hydrochloric acid solution into a 1000ml polytetrafluoroethylene reaction device; add 10g of lithium fluoride and stir until completely dissolved; then add 10g of carbon aluminum titanium (Ti3AlC2) and react at 40°C for 50 hours. After the reaction, use an ultrasonic machine to perform ultrasonic stripping, use a high-speed centrifuge to centrifuge, and perform ultrasonic stripping and centrifugation 22 times in deionized water, and then dry to obtain MXene black powder.

[0029] S2: Pour 750 ml of deionized water into a three-necked flask, add 2.37 g of potassium permanganate, and after it is fully dissolved, add 200 ml of ethyl acetate, stir at room temperature, and react for 15 hours until the red color of the solution fades, place it in a high-speed centrifuge for centrifugation, and then wash it alternately with deionized water and ethanol three times; after washing, place it in a vacuum drying oven and dry it at 80°C for 8 hours to obtain solid particles; finally, grind the solid particles to obtain δ-MnO2 nanosheet powder.

[0030] S3: 0.5 g of the MXene black powder obtained in step S1 was dispersed in 500 ml of deionized water (mass fraction of 0.1 wt%) and mechanically stirred to achieve complete dispersion; then, 100 ml of a chitosan solution with a mass fraction of 0.1 wt% (pH adjusted to 5) was dropped into the solution, and after continuous stirring for 2 hours, the suspension was centrifuged and washed with deionized water to obtain an intermediate product; S4: The δ-MnO2 nanosheet powder obtained in step S2 is added to deionized water to prepare a MnO2 suspension with a concentration of 0.2wt%; under stirring and ultrasound, the intermediate product obtained in step S3 is dispersed into 500ml of deionized water, and slowly dripped into the pre-prepared 100ml of the above-mentioned 0.2wt% MnO2 suspension. After stirring for 2 hours, it is centrifuged and washed three times, and dried in a forced air drying oven at 80°C, and finally ground to obtain MXene@CHS@MnO2 solid powder.

[0031] like Figure 2 As shown in FIG. 1 , the TEM image of the ultrathin MXene prepared in step S1 of this embodiment is shown. The results show that a thinner MXene nanosheet structure can be obtained by multiple ultrasonic exfoliation techniques. The X-ray diffraction pattern, TEM image, EDX spectrum and powder photo of the prepared MXene@CHS@MnO2 are shown in FIG. Figure 3 , 4 , 5, and 7 show the successful preparation of the catalytic detoxification agent composite material. Figure 6 It can be seen from the line scanning curve in that the core part of the catalyst detoxifier is mainly composed of MXene, and MnO2 nanosheets are successfully coated on the surface of MXene. The transmission electron microscopy image and line scanning curve clearly show that the obtained catalyst detoxifier has a sandwich structure and exhibits good stability.

[0032] Secondly, the formulation and preparation method of introducing the catalytic detoxifier based on MXene nanosheet material into the rigid polyurethane foam composite material are as follows: Rigid polyurethane foam (RPUF) and its modified products were prepared by a one-step foaming method. The specific formula is shown in Table 1.

[0033] Step a: Add 100g of polyol LY4110 into a 250ml disposable paper cup, add 1g of amine catalyst A33, 0.5g of organotin catalyst LC, 1.5g of deionized water, 2g of silicone oil and 3g of triethanolamine in sequence, and stir well with a stirrer to obtain a white material; Step b: Add the prepared catalyst detoxifier to 143.6 g of polymethylene polyphenyl polyisocyanate (PAPI) and disperse it by mechanical stirring for 30 minutes; then, pour the dispersion into the white material obtained in step a, stir vigorously for about 10 seconds, and quickly pour the mixture into a pre-prepared stainless steel mold (size 250×150×60mm³), allow it to foam freely and mature in an oven at 80°C for 12 hours to finally obtain RPUF / MXene@CHS@MnO2 nanocomposite material.

[0034] Table 1 Formula components of rigid polyurethane foam and its composite materials Samples RPUF-1 RPUF-2 RPUF-3 RPUF-4 RPUF-5 RPUF-6 Polyol LY4110 (g) 100 100 100 100 100 100 Amine catalyst A33 (g) 1 1 1 1 1 1 Organotin Catalyst LC (g) 0.5 0.5 0.5 0.5 0.5 0.5 Deionized water (g) 1.5 1.5 1.5 1.5 1.5 1.5 Silicone oil (g) 2 2 2 2 2 2 Triethanolamine(g) 3 3 3 3 3 3 MXene 0 0 5.1 0 0 0 <![CDATA[MnO2]]> 0 0 0 5.1 0 0 <![CDATA[MXene / CHS / MnO2]]> 0 0 0 0 5.1 10.5 PM-200 (g) 143.6 143.6 143.6 143.6 143.6 143.6 Example 2 The preparation method of the catalyst detoxifier and modified rigid polyurethane foam composite material based on MXene nanosheet material in this embodiment is as follows: First, the MXene@CHS@MnO2 catalyst detoxifier was prepared according to the following steps: S1: 150 ml of concentrated hydrochloric acid was slowly drained into 50 ml of deionized water to prepare a hydrochloric acid solution, which was then poured into a 1000 ml polytetrafluoroethylene reaction device; 10 g of lithium fluoride was added and stirred until completely dissolved; then 10 g of carbon aluminum titanium (Ti3AlC2) was added and reacted at 40°C for 50 hours. After the reaction, ultrasonic stripping was performed using an ultrasonic machine, and then centrifugal separation was performed using a high-speed centrifuge. After 26 times of ultrasonic stripping and centrifugal separation in deionized water, MXene black powder was obtained by drying.

[0035] S2: Pour 750 ml of deionized water into a three-necked flask, add 2.37 g of potassium permanganate, and after it is fully dissolved, add 200 ml of ethyl acetate, heat to 90 ° C, stir, and react for 15 hours until the red color of the solution fades. Subsequently, place it in a high-speed centrifuge for centrifugation, and then wash it alternately with deionized water and ethanol three times; after washing, place it in a vacuum drying oven and dry it at 80 ° C for 8 hours to obtain solid particles; finally, grind the solid particles to obtain δ-MnO2 nanosheet powder.

[0036] S3: 1.5 g of the MXene black powder obtained in step S1 was dispersed in 500 ml of deionized water with a mass fraction of 0.3 wt%, and mechanically stirred to achieve complete dispersion; then, 100 ml of chitosan solution with a mass fraction of 0.3 wt% (pH adjusted to 5) was dropped; after continuous stirring for 2 hours, the suspension was centrifuged and washed with deionized water to obtain an intermediate product.

[0037] S4: The δ-MnO2 nanosheet powder obtained in step S2 is added to deionized water to prepare a MnO2 suspension with a concentration of 0.6wt%; under stirring and ultrasound, the intermediate product obtained in step S3 is dispersed into 500ml of deionized water, and slowly dripped into the pre-prepared 100ml of the above-mentioned 0.6wt% MnO2 suspension. After stirring for 2 hours, it is centrifuged and washed six times, and finally dried in a forced air drying oven at 80°C, and finally ground to obtain MXene@CHS@MnO2 solid powder.

[0038] Next, the modified rigid polyurethane foam composite material was prepared. The formula of the RPUF / MXene@CHS@MnO2 nanocomposite material in parts by mass in this embodiment is shown in Table 2: Table 2 RPUF / MXene@CHS@MnO2 nanocomposite formulation Samples RPUF-1 RPUF-2 RPUF-3 RPUF-4 RPUF-5 RPUF-6 Polyol LY4110 (g) 100 100 100 100 100 100 Amine catalyst A33 (g) 1 1 1 1 1 1 Organotin Catalyst LC (g) 0.5 0.5 0.5 0.5 0.5 0.5 Deionized water (g) 1.5 1.5 1.5 1.5 1.5 1.5 Silicone oil (g) 2 2 2 2 2 2 Triethanolamine(g) 3 3 3 3 3 3 <![CDATA[MXene / CHS / MnO2]]> 0 2.5 5.1 7.8 10.5 13.2 PM-200 (g) 143.6 143.6 143.6 143.6 143.6 143.6 According to the formula shown in Table 2, different mass fractions of MXene@CHS@MnO2 catalyst detoxifier were added to the black material of rigid polyurethane foam. After mechanical stirring for 30 minutes, the mixture was added to the white material and fully stirred for 10 seconds using a high-speed mechanical stirrer. Then, the mixture was poured into a fixed mold with a size of 250×150×60 mm³ for free foaming. After the foam was launched, it was placed in an oven at 80°C for aging for 12 hours to complete the polymerization reaction, thereby obtaining RPUF / MXene@CHS@MnO2 nanocomposite materials.

[0039] Finally, the prepared modified rigid polyurethane foam composite material was tested, and the mechanical properties of the RPUF composite material were characterized by a universal tensile machine. Figure 8 As shown, Figure 8 (a) is the force-displacement curve of pure rigid polyurethane foam. Figure 8(b) is the force-displacement curve of rigid polyurethane foam / MXene@CHS@MnO2 nanocomposite. After the introduction of MXene@CHS@MnO2 catalytic detoxifier, the compression performance of RPUF is significantly enhanced. In addition, the addition of 4 wt% MXene@CHS@MnO2 catalytic detoxifier can reduce the total smoke particle release of RPUF nanocomposite by 63%, the peak heat release rate by 34%, and show a significant carbonization effect. It can be seen that the application of the constructed MXene nanosheet material-based catalytic detoxifier in rigid polyurethane foam materials can effectively inhibit smoke generation and improve the catalytic carbonization effect.

[0040] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A catalyst detoxifier based on MXene nanosheet material, characterized in that: It includes a carrier layer, a detoxification functional layer and a catalytic barrier layer. The carrier layer is a MXene nanosheet. The detoxification functional layer is composed of biomass material deposited on the surface of the MXene nanosheet by electrostatic adsorption. The catalytic barrier layer is composed of MnO2 electrostatically adsorbed on the surface of the detoxification functional layer, thereby forming a core-shell-outer layer sandwich structure.

2. A catalyst detoxifier based on MXene nanosheet material according to claim 1, characterized in that , the thickness of the MXene nanosheet is 1-10 nanometers.

3. A catalyst detoxifier based on MXene nanosheet material according to claim 1, characterized in that , the biomass material includes chitosan, cationic starch or plant protein.

4. A catalyst detoxifier based on MXene nanosheet material according to claim 1, characterized in that , the crystal structure of the MnO2 is δ-MnO2.

5. A method for preparing a catalyst detoxifier based on MXene nanosheet material as described in any one of claims 1 to 4, characterized in that , including the following steps: S1. Preparation of MXene nanosheets: Pour hydrochloric acid solution into a polytetrafluoroethylene reactor, add lithium fluoride, add carbon, aluminum and titanium after it is dissolved, react at a set temperature, ultrasonically peel, centrifuge and dry; S2. Preparation of δ-MnO2 nanosheets: dissolve potassium permanganate completely in deionized water, add ethyl acetate after it is completely dissolved, stir, react until the red color completely disappears, then centrifuge, wash, and dry; S3, preparing a detoxification functional layer: dispersing the MXene nanosheets obtained in step S1 in deionized water, then dropping a chitosan aqueous solution, centrifuging the suspension after mechanical stirring, and washing to obtain an intermediate product; S4. Preparation of a catalytic barrier layer: Under stirring and ultrasonic action, the intermediate product obtained in step S3 is dispersed in deionized water, and then dripped into the suspension of MnO2 obtained in step S2. After stirring, the suspension is centrifuged, washed, and dried.

6. The method for preparing a catalyst detoxifier based on MXene nanosheet material according to claim 5, characterized in that In step S1, the concentration of the hydrochloric acid solution is 8-10 mol / L, the set temperature is 35-45°C, the reaction time is 40-50h, and the ultrasonic stripping and centrifugal separation treatments are performed for no less than 20 times.

7. The method for preparing a catalyst detoxifier based on MXene nanosheet material according to claim 5, characterized in that In step S3, the pH value of the chitosan aqueous solution is 5-5.5, and the acid used to adjust the pH value of the chitosan aqueous solution is dilute hydrochloric acid or dilute sulfuric acid.

8. The method for preparing a catalyst detoxifier based on MXene nanosheet material according to claim 5, characterized in that ,In step S3, the MXene concentration is 0.1wt%-0.5wt%, and the chitosan concentration is 0.1wt%-1wt%.

9. A modified rigid polyurethane foam composite material, characterized in that , including a catalytic detoxifier based on MXene nanosheet materials as described in any one of claims 1-4.

10. A method for preparing the modified rigid polyurethane foam composite material as claimed in claim 9, characterized in that , including the following steps: a: adding an organotin catalyst, an amine catalyst, silicone oil, deionized water and triethanolamine to the polyol, stirring evenly to obtain a white material; b: Add the catalyst detoxifier to the isocyanate, disperse it by mechanical stirring, and then pour the dispersion into the white material obtained in step a. After stirring, pour the mixture into a mold, allow it to foam freely, and mature it in an oven.